Quantitative trait loci for response to ethanol in an intercontinental set of recombinant inbred lines of Drosophila melanogaster - Defays, Raquel (2012)
Alcohol, a drug widely abused, impacts the central nervous system functioning of diverse organisms. The behavioral responses to acute alcohol exposure are remarkably similar among humans and fruit ﬂies. In its natural environment, rich in fermentation products, the fruit ﬂy Drosophila melanogaster encounters relatively high levels of ethanol. The effects of ethanol and its metabolites on Drosophila have been studied for decades, as a model for adaptive evolution. Although extensive work has been done for elucidating patterns of genetic variation, substantially less is known about the genomic regions or genes that underlie the genetic variation of this important trait. To identify regions containing genes involved in the responses to ethanol, we used a mapping population of recombinant inbred (RIL) lines to map quantitative trait loci (QTL) that affect variation in resistance and recovery from ethanol sedation in adults and ethanol resistance in larvae. We mapped fourteen QTL affecting the response to ethanol on the three chromosomes. Seven of the QTL inﬂuence the resistance to ethanol in adults, two QTL are related to ethanol-coma recovery in adults and ﬁve affect the survival to ethanol in larvae. Most of the QTL were trait speciﬁc, suggesting that overlapping but generally unique genetic architectures underlie each trait. Each QTL explained up to 16.8 % of the genetic variance among lines. Potential candidate loci contained within our QTL regions were identiﬁed and analyzed.